LEADERSHIP IDENTITY CONSTRUCTION: AN EXPLORATORY EMBEDDED MULTIPLE CASE-STUDY OF HEADS OF DEPARTMENTS IN TWO SCHOOLS IN KAZAKHSTAN - Badanova, Aisulu (Nazarbayev University Graduate School of Education, 2024)
Educational systems around the world are focused on enhancing the quality and equity in education. Kazakhstan, with aspirations to rank among the 30 most developed economies by 2050, recognizes the role of education in developing competitive human capital for economic growth. Thus, the nation initiated rapid educational changes aimed at improving the teaching and learning quality and standards in schools. Despite ongoing decentralization efforts, the Kazakhstani education system remains centralized and bureaucratic due to the legacy of the Soviet era, which is still present in teachers’ memories and professional beliefs, and internal structures of the school system including school administration, leadership and management. While traditionally, school leadership has been solely associated with school principal, there has been a shift towards more distributed forms of leadership. Middle leaders, particularly heads of departments (HoDs), are well placed in between the policy and practice and teachers and senior leaders. They can play a pivotal role in enacting leadership within schools. Their leadership potential to impact the improvement of teaching and learning practices, contribute to the overall school improvement, and negotiate and interpret school reforms has been increasingly recognized worldwide.
Көшбасшылық бірегейлікті қалыптастыру: Қазақстандағы екі мектептің әдістемелік бірлестік жетекшілерінің сапалық кейс-стади зерттеуі
Формирование лидерской идентичности: Качественное множественное кейс-стади руководителей методических объединений в двух школах в Казахстане
Keywords: Type of access: Embargo; school leadership; middle leaders; heads of department; leadership identity construction